A Vila Belga e suas tipologias: promoção e valorização do patrimônio cultural ferroviário na cidade de Santa Maria, RS - Socal, Ana Júlia Scortegagna (2023)
Vila Belga is a set of buildings located in Santa Maria, Rio Grande do Sul, which has its origin intrinsically related to the arrival of the railroad in the city. Built at the beginning of the 20th century to accommodate the workers of the Belgian company responsible for leasing a large part of the state railway, Vila Belga currently has 80 remaining units divided into different typologies. This study, developed in the Graduate Program in Cultural Heritage within the thematic area Architecture and Material Heritage and the research line Preservation of Material Heritage, had the general objective of contributing to the promotion and valorization of Vila Belga based on the elaboration of an e-book about the complex, with emphasis on the different existing typologies. As specific objectives, the study aimed to: understand the importance of Vila Belga as a cultural heritage of Santa Maria; identify the historical and architectural aspects of the complex; identify the different typologies and their specific characteristics. Through an qualitative approach based on an exploratory-descriptive methodology, the study was divided into three stages: (1) bibliographical and documentary research; (2) organization and production of graphic materials and (3) elaboration of the final product, corresponding to an e-book about Vila Belga. Seven typologies with three variations were identified and the aspects that differentiate them are related to the layout, location of the main access, number of bedrooms, number of openings and the presence or absence of pilasters on the front facade. Regardind the architectural attributes, it was observed that some elements vary between typologies while others are used to differentiate the buildings. It was concluded that the constructive characteristics of Vila Belga added to its participation in the history of Santa Maria, mainly due to the railroad, make the complex an important cultural heritage of the city.